2020
DOI: 10.21203/rs.3.rs-79465/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The long-term protective effect of tadalafil on spermatogenesis following testicular ischemia-reperfusion injury in a rat model

Abstract: Background Testicular torsion is a urological emergency in which misdiagnosis and inappropriate treatment can lead to testicular atrophy and male infertility owing to ischemia-reperfusion injury (IRI). Although experimental studies of testicular torsion have been preceded, promising therapeutic agents based on the long-term effect for spermatogenesis have not been identified in testicular ischemia reperfusion injury (IRI) animal model. Tadalafil, one of the phosphodiesterase-5 inhibitors commonly used in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Previously, we conducted a study on adolescent rats to identify the ischemic duration that would result in serious long-term histopathologic changes after testicular IRI. Histopathologic analysis performed four weeks after testicular IRI confirmed there was serious deterioration in spermatogenic activity after three hours of ischemia, but not after shorter ischemic durations [31]. For the current study we therefore selected three hours of ischemia as the duration of torsion in order to study the long-term effects on spermatogenesis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously, we conducted a study on adolescent rats to identify the ischemic duration that would result in serious long-term histopathologic changes after testicular IRI. Histopathologic analysis performed four weeks after testicular IRI confirmed there was serious deterioration in spermatogenic activity after three hours of ischemia, but not after shorter ischemic durations [31]. For the current study we therefore selected three hours of ischemia as the duration of torsion in order to study the long-term effects on spermatogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…The rats were then euthanized using carbon dioxide gas or cervical dislocation. In a previous study with a rat testicular torsion model, we found that testicular damage was aggravated in an ischemic time-dependent manner, and that serious deterioration of spermatogenic activity developed three hours after ischemia [31]. Therefore, three hours of ischemia was selected as the torsion duration period for the present study.…”
Section: Methodsmentioning
confidence: 99%